Introducing UNIX and Linux - Mike Joy (Grassroots (Lagos, Nigeria), 2002)
An introductory, tutorial style text covering the basics of UNIX and Linux for the complete beginner, this is a comprehensive and well written introduction to these operating systems. UNIX and Linux are two of the most commonly used operating systems within the educational and corporate worlds and are growing in popularity